Early‐onset group B streptococcal disease in a risk factor‐based prevention setting: A 15‐year population‐based study. (11th September 2018) - Chen, Julie C.; Jenkins‐Marsh, Sue; Flenady, Vicki; Ireland, Susan; May, Meryta; Grimwood, Keith; Liley, Helen G.
Abstract : Background: Intrapartum chemoprophylaxis reduces early‐onset group B streptococcal disease (EOGBSD) in newborns. Some guidelines advise that intrapartum antibiotics should be offered following universal antenatal screening for GBS carriage and others recommend intrapartum antibiotics based on clinical risk factors alone. Since 1999, Queensland guidelines have recommended a risk factor‐based approach. We examined trends in EOGBSD rates over time in Queensland in the setting of these guidelines and whether management of cases reflected the recommendations. Methods: A state‐wide retrospective search of pathology databases, allowing near‐complete, population‐based case identification, was conducted to detect live‐born infants from January 2000 to December 2014 with GBS cultured from blood or cerebrospinal fluid within seven days of age. A nested audit of EOGBSD cases comparing two epochs, 2000–2010 and 2011–2014, was performed to determine patient characteristics and guideline adherence for each case. Results: Mean incidence of EOGBSD in Queensland from 2000 to 2014 was 0.33 per 1000 live births (SD± 0.08) with no changing trend over time. The case‐mortality rate in the 2011–2014 epoch was 1.2% compared to 11.9% in 2000–2004 (odds ratio (OR) 0.09, 95% confidence interval (CI) 0.002–0.67). The proportion of EOGBSD cases who were preterm infants decreased from 29.8% to 13.3% (OR 0.36, 95% CI 0.14–0.84). Of cases with risk factors in the 2011–2014 epoch, 46% received intrapartum antibiotics compared to 25% in 2000–2004 (OR 2.49, 95% CI 0.86–7.58, P = 0.09). Conclusions: EOGBSD incidence rate in Queensland remained low during 2000–2014. However, both the 2011–2014 case‐mortality rate and the proportion of preterm cases significantly decreased. Missed opportunities for intrapartum chemoprophylaxis remain.